Fluidic Membrane Processing: Fluidic Processing of High‐Performance ZIF‐8 Membranes on Polymeric Hollow Fibers: Mechanistic Insights and Microstructure Control (Adv. Funct. Mater. 28/2016). (25th July 2016) - Eum, Kiwon; Rownaghi, Ali; Choi, Dalsu; Bhave, Ramesh R.; Jones, Christopher W.; Nair, Sankar
Abstract : On page 5011, S. Nair and co‐workers show that metal‐organic framework membranes, grown by non‐isothermal fluidic processing techniques on the inner surfaces of polymeric hollow fiber supports, efficiently separate molecular mixtures such as propylene from propane by size‐ and shape‐selective sieving through their subnanometer pores. Illustration credit : Younghee Kim, Kiwon Eum, and Sankar Nair.